Choosing the Best Treatment Approach for Axial Vein Reflux: Thermal versus Nonthermal Approaches - Shmelev, Karen; Gupta, Ramona (Seminars in Interventional Radiology, 2021)
Chronic venous insufficiency is a common and treatable medical condition which has a high morbidity if left untreated, progressing to lower extremity edema, skin changes of lipodermatosclerosis, and venous ulceration. Treatment options have significantly expanded over the last several decades, shifting away from the traditional surgical approach to more minimally invasive procedures such as endoluminal venous laser ablation or radiofrequency ablation. Even more recently, several techniques using nonthermal methods to ablate varicose veins have been developed, which offer the advantage of not requiring labor-intensive and painful tumescent anesthesia to protect the surrounding tissues. These techniques include mechanochemical ablation, cyanoacrylate closure, or polidocanol microfoam injection and can be offered to a wider range of patients without the need for sedation while offering similar closure rates and improved postprocedure symptom profile. Furthermore, certain patient characteristics which might preclude or complicate the use of thermal ablation methods might not pose a problem with nonthermal nontumescent methods.
Keywords: Thermal tumescent; nonthermal nontumescent; axial vein reflux; interventional radiology